Understanding computers : today and tomorrow - Morley, Deborah; Parker, Charles S., 1945- (Boston, Mass. : Course Technology/Cengage Learning, 2011)
Understanding Computers: Today and Tomorrow, International Edition gives your students a classic introduction to computer concepts with a modern twist! Known for its emphasis on industry insight, this text makes concepts relevant to todays career-focused students.
"Comprehensive."
Includes index.
Keywords: Computers; Electronic data processing